Hypothalamic Irak4 is a genetically controlled regulator of hypoglycemia-induced glucagon secretion - Alexandre Picard; Xavier Berney; Judit Castillo-Armengol; David Tarussio; Maxime Jan; Ana Rodriguez Sanchez-Archidona; Sophie Croizier; Bernard Thorens (Elsevier, 2022)
Objectives: Glucagon secretion to stimulate hepatic glucose production is the first line of defense against hypoglycemia. This response is triggered by so far incompletely characterized central hypoglycemia-sensing mechanisms, which control autonomous nervous activity and hormone secretion. The objective of this study was to identify novel hypothalamic genes controlling insulin-induced glucagon secretion. Methods: To obtain new information on the mechanisms of hypothalamic hypoglycemia sensing, we combined genetic and transcriptomic analysis of glucagon response to insulin-induced hypoglycemia in a panel of BXD recombinant inbred mice. Results: We identified two QTLs on chromosome 8 and chromosome 15. We further investigated the role of Irak4 and Cpne8, both located in the QTL on chromosome 15, in C57BL/6J and DBA/2J mice, the BXD mouse parental strains. We found that the poor glucagon response of DBA/2J mice was associated with higher hypothalamic expression of Irak4, which encodes a kinase acting downstream of the interleukin-1 receptor (Il-1R), and of Il-ß when compared with C57BL/6J mice. We showed that intracerebroventricular administration of an Il-1R antagonist in DBA/2J mice restored insulin-induced glucagon secretion; this was associated with increased c-fos expression in the arcuate and paraventricular nuclei of the hypothalamus and with higher activation of both branches of the autonomous nervous system. Whole body inactivation of Cpne8, which encodes a Ca++-dependent regulator of membrane trafficking and exocytosis, however, had no impact on insulin-induced glucagon secretion. Conclusions: Collectively, our data identify Irak4 as a genetically controlled regulator of hypoglycemia-activated hypothalamic neurons and glucagon secretion.